Izpol'zovanie nauchnykh brazrabotok v sfere fizicheskoi kul'tury i sporta - Vinogradov, P. A.; Popov, I. V. (Teorija i Praktika fiziceskoj Kul'tury, 1999)
It has been examined the actual situation concerning the use and utilization of scientific works and results in physical culture and sports in Russia.